DEVELOPMENT OF PROTEIN CONCENTRATION DETERMINATION WORKSHEETS USING THE COLORIMETER FREE APPLICATION - Ida Farida; Saepudin Rahmatullah (Gunung Djati Conference Series, 2021)
This research is motivated by the importance of science process skills in determining protein concentration. Science process skills can be supported by the existence of effective and efficient worksheets and technological contributions. The free ColorMeter application can be used for colorimetric protein analysis. This study aims to describe the appearance of the worksheet and to analyze the results of the validation test. Worksheets are arranged based on indicators of science process skills, namely the skills to ask questions, formulate hypotheses, design experiments, observe, apply concepts, conclude and communicate. The research method used in the preparation of the worksheet is the R&D method. The validation test is carried out using a questionnaire that contains a worksheet display statement. The results of the validation test carried out obtained an average value of rcount of 0.91 with a valid worksheet description and can be used as a practicum guide.